Precipitation Variations in the Flood Seasons of 1910–2019 in Hunan and Its Association With the PDO, AMO, and ENSO - Zeng, Yuxing; Huang, Chao; Tang, Yihao; Peng, Jiadong (Frontiers in Earth Science, 2021)
Based on the monthly precipitation data in Hunan from1910 to 2019), the interdecadal variation characteristics of the precipitation in the flood season of Hunan (April–September) and the relationship with the Pacific decadal oscillation (PDO), Atlantic Multidecadal Oscillation (AMO) and El Niño-Southern Oscillation (ENSO) are detailedly analyzed. The results show that the precipitation in Hunan flood seasons shows an interdecadal oscillation with a period of about 20 years, which is caused by the joint effect of the PDO and AMO. If the PDO and AMO are in the same phase, the corresponding Hunan flood season is characterized by more precipitation, and conversely, it is less precipitation. Further analyses show that in the next year of the El Niño year, if the PDO and AMO are in the same positive phase, it is favorable for the west Pacific subtropical high (WPSH) to be stronger and more southward than normal. Such a weather situation is conducive to the water vapor transport to the southern China, and as a result there is more precipitation in most of the Hunan Province. If the PDO and AMO are in the same negative phase, the WPSH is weaker than normal, but the India-Burma trough is obviously stronger, which is also favorable for the southwesterly water vapor transport to the southern China. However, in the next year of the La Niña year, regardless of the phase combination of the PDO and AMO, the low latitude areas along the southern coast of China are controlled by a negative geopotential height anomaly and the WPSH retreats to the sea, which is not conducive to the northward transport of water-vapor, and the precipitation in Hunan Province is less than normal. But if only the cold SST background in the previous stage is considered (without reaching the standard of a La Niña event)，is more precipitation in most of the Hunan Province. Therefore, at the interannual scale, the PDO and AMO also have a modulating effect on the precipitation signal. However, the interannual-scale ENSO signal has a greater influence on the precipitation in Hunan flood seasons.